Let ( x 1 , y 1 ) , ( x 2 , y 2 ) , ( x 3 , y 3 ) , … , ( x n , y n ) be the ordered pairs of integers that satisfy the equation x 3 + y 3 = ( x + y ) 2 .
Express your answer as i = 1 ∑ n ( x i + y i ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
(0,0) is a solution. If x + y .ne. 0, we can divide both sided by x + y. Then x^2 - xy + y^2 = x + y, Writing as a quadratic in x, x^2 - (y + 1)x + y^2 - y = 0, with solution 2x = (y + 1) +/- sqrt(6y -3y^2 + 1). Letting D^2 = 6y - 3y^2 + 1, 3(y - 1)^2 + D^2 = 4. So y < 3.If y = 0, x = 1. If y = 1, x =0 or 2. If y = 2,x + 1 or 2. . So the ordered pairs are (0,0), (0,1), (1,0), (2,1), (1,2), (2,2). Adding all components, sum = 12. It can be shown that x or y cannot be <0.
Problem Loading...
Note Loading...
Set Loading...
Note that x 3 + y 3 − ( x + y ) 2 = ( x + y ) ( x 2 − ( y + 1 ) x + y 2 − y ) = 0 x + y = 0 gives infinite number of solutions in the form ( x , y ) = ( a , − a ) . For getting integer solutions from x 2 − ( y + 1 ) x + y 2 − y = 0 , which is a quadratic in terms of x , discriminant of quadratic must be non-negative: Δ = − 3 y 2 + 6 y + 1 ≥ 0 y = 0 , 1 , 2 Plugging the values of y in the quadratic gives ( x , y ) = ( 0 , 0 ) , ( 1 , 0 ) , ( 0 , 1 ) , ( 2 , 1 ) , ( 1 , 2 ) , ( 2 , 2 )